Gel with electric / magnetic dual stimulation response and preparation method thereof
By using materials such as chitosan in the field of soft robots to prepare gels with dual stimulation responses, the problems of insufficient safety in human daily life and unstable operation in unstructured environments are solved, and multiple response functions are realized in different environments, which are suitable for soft robot materials.
Patent Information
- Application Number
- CN202211317965.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-10-26
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2042-10-26
AI Technical Summary
Traditional rigid robots have safety problems in human daily life and are difficult to operate stably in unstructured environments. Soft robots can interact with humans more safely due to the softness of the material and high freedom of movement, but their multiple response functions in different environments are insufficient.
A gel with an electrical/magnetic dual stimulation response was prepared by cross-polymerization of chitosan, carboxymethyl chitosan, aminolated ferrotetraoxide, polyvinyl alcohol and cross-linking agent glutaraldehyde, and rapid non-contact remote control was achieved through the stimulation of electric and magnetic fields.
The gel can effectively respond to electric field stimulation in acidic and alkaline environments, has good magnetic field stimulation response capabilities, realizes fast deflection and remote magnetic field control at low voltages, and is suitable for soft robot materials. It has the characteristics of green and environmental protection, simple preparation and sensitive response.
Smart Images

Figure CN115678042B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of flexible materials and relates to a gel with electric / magnetic dual stimulation response and a preparation method thereof. Background Art
[0002] With the advancement of science and technology, robots have gradually entered the daily life of human beings from the traditional industrial field, and the interaction with humans has increased significantly. However, traditional robots are almost all made of rigid materials, which are very different from the elastic modulus of human tissues, so there will be great safety issues when rigid robots are used in human daily life. Secondly, since traditional rigid robots are mainly composed of discrete connecting rods and mechanical joints, it is difficult for them to operate stably in unstructured environments. Based on the above problems, soft robots came into being. Soft robots have an elastic modulus similar to that of human tissues, and are safer than traditional rigid robots in human-machine interaction. At the same time, due to the softness of its own constituent materials and ultra-high freedom of movement, soft robots do not need overly complex connection mechanism designs when designing and constructing, which enables them to handle various less complex operations more flexibly and stably in various unstructured environments.
[0003] Hydrogel is a three-dimensional network structure composed of hydrophilic polymer chains connected by physical or chemical action. It swells in water but does not dissolve. Due to its unique characteristics of high water absorption, high water retention, good biocompatibility, fast response speed, mechanical properties of a certain strength, and flexible texture, it can be used in various components of soft robots, such as actuators, sensors, hydrogel-based interactions, hydrogel-based soft energy, and soft computing circuits. Compared with traditional hydrogels, smart hydrogels can convert stimuli such as temperature, electric field, magnetic field, light, pH, enzymes, etc. into mechanical responses, which makes it have a broader prospect in the field of soft materials. At present, smart hydrogels have been preliminarily studied and applied in the fields of actuators, artificial muscles, and medical transmission. There have also been some attempts in the field of soft robots, such as robot grippers, robot fish, bionic flowers, and people doing sit-ups ([1] Jiang S, Liu F, Lerch A, et al: Unusual and superfast temperature-triggered actuators. Adv Mater. [2] Kim DY, Choi S, Cho H, et al: Electroactive soft photonic devices for the synesthetic perception of color and sound. Adv Mater. [3]. Qin M, Sun M, Bai R, et al: Bioinspired hydrogel interferometer for adaptive coloration and chemical sensing. Adv Mater. [4] Ren J, Zhang Y, Bai W, et al: Elastic and wearable wire-shaped lithium-ion battery with high electrochemical performance. Angew Chem Int Ed Engl. [5]. Lee HR, Woo J, Han SH, et al: A stretchable ionic diode from copolyelectrolyte hydrogelswith methacrylatedpolysaccharides.Advanced Functional Materials.).As the research deepened, people found that compared with single stimulus-responsive hydrogels, dual or even multiple stimulus-responsive hydrogels are more adaptable to working in different environments, and their functions have also changed from relatively single to diversified. Research and development of hybrid smart hydrogels with rapid response and multiple response functions has become the forefront of this field. Summary of the invention
[0004] The purpose of the present invention is to provide a gel with electric / magnetic dual stimulation response and a preparation method thereof. The gel can realize rapid non-contact remote control through electric field stimulation and magnetic field stimulation, and can be used as an excellent soft robot material.
[0005] The technical solution for achieving the purpose of the present invention is as follows:
[0006] The preparation method of the gel with dual electrical / magnetic stimulation response is obtained by cross-linking and polymerization of chitosan, carboxymethyl chitosan, amino-ferric tetroxide, polyvinyl alcohol and cross-linking agent glutaraldehyde, and the specific steps are as follows:
[0007] Step 1, preparation of Fe3O4 modified particles wrapped by aminated SiO2 (Fe3O4@SiO2-NH2): ultrasonically disperse Fe3O4@SiO2 in anhydrous ethanol, then add 3-aminopropyltriethoxysilane (KH550), heat to 90±5°C, stir and reflux for more than 12 hours, rinse repeatedly with ethanol and water in turn, and dry to obtain Fe3O4@SiO2-NH2;
[0008] Step 2, the chitosan solution and the carboxymethyl chitosan solution are mixed evenly, glutaraldehyde solution is added for cross-linking for 2±0.5h, and then polyvinyl alcohol (PVA) solution and Fe3O4@SiO2-NH2 are added, stirred until the mixture is evenly mixed, poured into a mold, and repeatedly frozen and thawed to obtain a Fe3O4@SiO2-NH2 composite gel.
[0009] Preferably, in step 1, the mass ratio of Fe3O4@SiO2 to KH550 is 1:1.1, g:mL.
[0010] Preferably, in step 2, the chitosan solution is a solution formed by dissolving chitosan in acetic acid solution, the concentration of chitosan is 0.04 g / ml, the concentration of acetic acid solution is 0.02 ml / ml, the concentration of carboxymethyl chitosan solution is 0.02 g / ml, the concentration of glutaraldehyde solution is 0.056 g / ml, the concentration of polyvinyl alcohol solution is 0.08 g / ml, and the mass ratio of chitosan, carboxymethyl chitosan, glutaraldehyde and polyvinyl alcohol is 120:40:1:160.
[0011] Preferably, in step 2, the number of repeated freezing and thawing operations is more than 3 times; during the repeated freezing and thawing process, the freezing temperature is -20°C, the freezing time is 24h, the thawing temperature is 26°C, and the thawing time is 4h.
[0012] Furthermore, the present invention also provides application of the Fe3O4@SiO2-NH2 composite gel in soft robots.
[0013] Compared with the prior art, the present invention has the following advantages:
[0014] In the gel system prepared by the present invention, chitosan and carboxymethyl chitosan both contain ionizable cationic group amino groups, so that when the gel is in a direct current electric field, it can produce a deflection toward the positive electrode in an acidic and neutral environment. At the same time, because carboxymethyl chitosan contains ionizable anionic groups, the gel can produce a deflection toward the negative electrode in response to direct current electric field stimulation in an alkaline environment. Moreover, because the gel system contains Fe3O4 magnetic particles, the gel can have a good magnetic field stimulation response while having an electric field stimulation response. The present invention adopts chemical crosslinking and physical crosslinking methods to prepare the gel material. The gel has a wide range of adaptability to acid-base environments, rapid deflection under low voltage, remote magnetic field control, and good reversibility and reproducibility. It is a green, environmentally friendly, simple to prepare, and responsive soft robot matrix material. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1 Infrared images of Fe3O4, Fe3O4@SiO2 and Fe3O4@SiO2-NH2.
[0016] Figure 2 The graph shows the electrical response test results of different composite gels at different pH values.
[0017] Figure 3 The electrical response curves of different composite gels under different actuation voltages.
[0018] Figure 4 This is a graph showing the electrical response test results of different composite gels under cyclic voltage.
[0019] Figure 5 Stress-strain curves and toughness diagrams of different composite gels.
[0020] Figure 6 Figure 2 shows different composite gel models and distortion deformation test results.
[0021] Figure 7 (a) Magnetically controlled bionic flower made of Fe3O4@SiO2-NH2 composite gel, (b) magnetically controlled gymnastic figure, and (c) object-finding and transporting diagram under magnetic control. DETAILED DESCRIPTION
[0022] The present invention is further described in detail below in conjunction with specific embodiments and drawings.
[0023] Example 1
[0024] (1) Preparation of Fe3O4 modified particles wrapped with silica: At room temperature, add 76g ethanol, 0.024g Fe3O4 and 24g deionized water to a 250mL flask in turn, use mechanical stirring, first heat to 50℃, stabilize for 15min, add 2.35g ammonium hydroxide (ammonia water), continue stirring for 10min, add a total of 400ul of tetraethyl orthosilicate (TEOS) in four batches, 100ul each time, and the interval between each two additions is 20min. Mechanical stirring for 24 hours, take out the sample, rinse it repeatedly with ethanol and deionized water 3 times each, the product is vacuum dried at 60℃, and the relatively pure Fe3O4@SiO2 composite nanoparticles are obtained after grinding.
[0025] (2) Take 1g of dried Fe3O4@SiO2 composite microspheres and add them into a 500ml three-necked round-bottom flask. Then add 300ml of anhydrous ethanol and disperse them by ultrasonic for 0.5h. Fe3O4@SiO2 :v KH550 =1:1.1, add KH550 solution, heat to 90℃, stir and reflux for 12 hours, rinse repeatedly with ethanol and deionized water, and obtain Fe3O4@SiO2-NH2 after drying.
[0026] Figure 1 The infrared scanning diagram of Fe3O4, Fe3O4@SiO2, and Fe3O4@SiO2-NH2 shows that at 564cm -1 At 1051cm -1 The Si-O-Si stretching vibration peak appeared, indicating that SiO2 was successfully bonded to the Fe3O4 surface, that is, Fe3O4@SiO2 was successfully prepared; -1 At , the characteristic peak of amino group appeared, indicating that the surface of magnetic particles was successfully modified by amino group, that is, Fe3O4@SiO2-NH2 was successfully prepared.
[0027] Example 2
[0028] In a 250 ml flask, add 19.5 ml of 0.04 g / ml chitosan solution and 12.5 ml of 0.02 g / ml carboxymethyl chitosan solution, heat to 50 °C in a water bath, stir mechanically until clear and transparent, add 2.5 ml of 0.005 g / ml glutaraldehyde solution, cross-link for 2 hours, then add 12.5 ml of 0.08 g / ml polyvinyl alcohol, at the same time, do not add magnetic particles, and add 2 g Fe3O4, 2 g Fe3O4@SiO and 2 g Fe3O4@SiO2-NH2 respectively, continue to stir until the mixture is uniform, pour into a mold, and freeze-thaw repeatedly to obtain basic gel, Fe3O4 composite gel, Fe3O4@SiO2 composite gel and Fe3O4@SiO2-NH2 composite gel.
[0029] like Figure 2 As shown, the electrical response behaviors of different composite gel systems at different pH values are as follows:
[0030] (1) The addition of unmodified Fe3O4 magnetic particles significantly reduced the electrical response ability and response stability of the gel. The maximum electrical response deflection angle in the acidic and neutral dielectric environments of pH = 3, 6, and 7 decreased by 54.3%, 33.3%, and 33.3%, respectively, with an average decrease of 40.8%; in the dielectric environments of pH = 7, 9, and 11, the gel could not stabilize at the maximum deflection angle and showed a rotation phenomenon; only in the strong alkaline environment of pH = 13 did a good electrical response deflection occur.
[0031] (2) By comparing the Fe3O4@SiO2 composite gel with the Fe3O4 composite gel, we found that the addition of Fe3O4 to the system after modification can greatly improve the negative impact of Fe3O4 particles on the electrical response ability of the electrical response basic system, and further enhance the electrical response ability of the gel in acidic and neutral environments, and make it have a more stable electrical response deflection in dielectric environments of pH = 7, 9, and 11. As shown in the figure, comparing the Fe3O4@SiO2 composite system with the Fe3O4 composite gel system, at pH = 3, the maximum electrical response deflection angle of the composite system increased from 55° to 130°, an increase of 136.3%; at pH = 6, the maximum electrical response deflection angle of the composite system increased from 60° to 120°, an increase of 100%; at pH = 7, the maximum electrical response deflection angle of the composite system increased from 20° to 88°, an increase of 340%; in an acidic environment, the maximum deflection angle increased by an average of 192.1%. It can be seen from the figure that the acid-base range in which the Fe3O4 composite gel system shows unstable deflection is from pH=7 to pH=11, a total of 5 pH spans, while the unstable range of the Fe3O4@SiO2 composite system may only appear in a very small range between pH=9 and pH=11.
[0032] (3) By comparing the Fe3O4@SiO2-NH2 composite system with the Fe3O4 composite gel system, we found that the addition of Fe3O4@SiO2-NH2 modified particles can improve the negative effect of Fe3O4 particles on the electrical response ability of the electrical response basic system. As shown in the figure, compared with the Fe3O4 composite gel system, the maximum deflection angle of the electrical response of the Fe3O4@SiO2-NH2 composite system increased from 55° to 90° at pH = 3, an increase of 63.6%; at pH = 6, the maximum deflection angle of the electrical response increased from 60° to 90°, an increase of 66.7%; at pH = 7, the maximum deflection angle of the electrical response increased from 20° to 80°, an increase of 300%; in an acidic environment, the maximum deflection angle increased by an average of 143.2%. Compared with the unstable intervals of the Fe3O4 composite gel system from pH=7 to pH=11, which have a total of 5 pH spans, the unstable range of the Fe3O4@SiO2-NH2 composite system can only appear in a very small range between pH=9 and pH=11.
[0033] (4) By comparing the Fe3O4@SiO2 composite system and the Fe3O4@SiO2-NH2 composite system, we found that the Fe3O4@SiO2 composite system has a larger electrical response deflection angle in acidic, neutral and weakly alkaline environments. In a strong alkaline environment, the Fe3O4@SiO2-NH2 composite system has a larger electrical response deflection angle. However, compared with the unmodified Fe3O4, both can better avoid the negative impact of the addition of magnetic particles on the electrical response performance of the original gel system.
[0034] By comparing the electrical response behaviors of the three particles under different pH environments, the following conclusions were drawn: First, the modified magnetic particles Fe3O4@SiO2 and Fe3O4@SiO2-NH2 can avoid the problem of a significant decrease in the maximum deflection angle of the electrical response of the gel in an acidic environment caused by the introduction of Fe3O4 particles; secondly, compared with the Fe3O4 composite gel system, the Fe3O4@SiO2 composite gel system and the Fe3O4@SiO2-NH2 composite gel system have more stable deflection orientations, and will not exhibit a large range of unstable electrical response behaviors.
[0035] The gel prepared by the present invention is a low voltage response gel. To ensure the safety of the gel when interacting with people, it is necessary to ensure that the gel has good electrical response capability within the 36V human body safety voltage. Figure 3 As shown in the figure, the electrical response behaviors of different gel systems were tested at 1v, 10v, 20v, and 30v to verify their electric field stimulation response capabilities at different voltage stages (the dielectric solution was 0.01mol / L NaCl solution). Figure 3As shown in the figure, after adding the unmodified Fe3O4 particles, the maximum deflection angle of the gel at each actuation voltage is greatly reduced compared with the original basic system; the addition of modified magnetic particles Fe3O4@SiO2 and Fe3O4@SiO2-NH2 not only avoids the decrease in the maximum deflection angle of the gel due to the addition of magnetic particles, but also can further improve the electrical response ability of the gel at each actuation voltage.
[0036] Place the gel strip in a 0.01 mol / L NaCl solution, first apply a forward voltage of 25 V to it, so that it deflects from its original position by 0° to 90° (or 60°, because the maximum deflection angle of the Fe3O4 composite system in a neutral dielectric solution is only 60°), and then apply a reverse voltage of -25 V to restore it from the original deflection angle of 90° (or 60°) to 0°. This is recorded as a voltage deflection cycle, and the time taken for the gel strip to complete a deflection cycle is recorded.
[0037] like Figure 4 As shown in the figure, the four systems were subjected to fatigue tests for 15 voltage cycles. As shown in the figure, after 15 voltage cycles, the basic system, the Fe3O4 composite system and the Fe3O4@SiO2-NH2 composite system were still able to reach the predetermined deflection angle and complete the cycle, and the electrical response ability did not show a significant decrease. However, the Fe3O4@SiO2 composite system could no longer return to its original position at the twelfth electrical response cycle, and finally completely lost its electrical response ability at the thirteenth voltage cycle. It can be seen that the addition of Fe3O4@SiO2 significantly reduces the fatigue resistance of the gel.
[0038] In order to explore the effect of adding different magnetic particles on the mechanical properties of the gel, a tensile test was performed. Figure 5 As can be seen in (a), after the unmodified magnetic particles Fe3O4 were added to the gel system, although the elongation did not increase, the tensile strength was improved to a certain extent, and the tensile strength of the gel increased from 46.7KPa to 60.3KPa, an increase of 29.1%; further, the addition of modified magnetic particles Fe3O4@SiO2 not only increased the tensile strength of the gel from 46.7KPa to 55.6KPa, an increase of 19.1%, but also increased the elongation at break from 255% to 271.7%, an increase of 6.5%. Similarly, the addition of modified magnetic particles Fe3O4@SiO2-NH2 increased the elongation at break and the fracture strength of the gel, and the tensile strength increased from 46.7KPa to 57.4KPa, an increase of 22.9%, and the tensile length increased from 255% to 284.1%, an increase of 11.4%. At the same time, the toughness of the gel after adding different magnetic particles was studied, such as Figure 5As shown in (b), the addition of magnetic particles can improve the toughness of the gel, among which Fe3O4, Fe3O4@SiO2, and Fe3O4@SiO2-NH2 can improve the toughness of the gel by 49.4%, 69.3%, and 83.8%, respectively. Therefore, the addition of magnetic functional particles not only gives the gel magnetic responsive functionality, but also promotes the enhancement of the toughness of the gel. Taking all factors into consideration, the addition of Fe3O4@SiO2-NH2 has the best effect on enhancing the mechanical properties of the hydrogel.
[0039] The realization of specific functions of soft robots depends largely on the molding of their functional shapes. Excellent moldability is the basis for giving gel materials more functional structures. Without good moldability, no matter how excellent the response performance is, it cannot be fully utilized, or even its performance will be useless. Therefore, as the matrix of soft robots, gel materials must have good moldability. Figure 6 As shown in (a), through the mold, the Fe3O4@SiO2-NH2 composite gel material was prepared into various structural models of different shapes and sizes, such as flat flowers, fish tails covered with scales, cute shells, stretched starfish, concave and convex spiral conchs, and super miniature speedwell flowers. Figure 6 As shown in (b), the Fe3O4@SiO2-NH2 composite gel material not only has excellent formability, but also has good distortion and deformation capabilities, making it suitable for various application environments.
[0040] In order to verify the feasibility of the gel in practical applications, a series of application experiments were carried out on the cast gel. Figure 7 (a) is a bionic simulation of a small gel flower cast in a mold, which slowly blooms under magnetic control. The greater the magnetic force, the tighter the petals close. When the magnet moves away, the magnetic force becomes smaller, and the traction on the gel flower becomes smaller and smaller, and the flower slowly blooms. Figure 7 (b) A starfish doing gymnastics under magnetic control. Applying magnetic force in different areas will get responses from different parts of the starfish, which provides realistic support for the realization of precise magnetic control of gels in the future. Figure 7 (a) and (b) are simple controls. Figure 7 (c) shows a more complex gel behavior control. Under magnetic traction, the soft gel robot gripper completes a series of operations such as searching, gripping, transporting, placing, and returning to the task. The execution of this series of tasks depends on the pre-control of the magnetic force. The precise magnetic control brings about precise gel movements, which also makes a preliminary attempt for the development of programmable magnetically controlled soft robots.
Claims
1. A method for preparing a gel having dual electrical / magnetic stimulation response, characterized in that: The specific steps are as follows: Step 1, preparation of Fe3O4@SiO2-NH2: ultrasonically disperse Fe3O4@SiO2 in anhydrous ethanol, then add KH550, heat to 90±5°C, stir and reflux for more than 12 hours, rinse repeatedly with ethanol and water in turn, and dry to obtain Fe3O4@SiO2-NH2; Step 2, mix the chitosan solution and the carboxymethyl chitosan solution evenly, add glutaraldehyde solution to cross-link for 2±0.5h, then add polyvinyl alcohol solution and Fe3O4@SiO2-NH2, stir until mixed evenly, pour into a mold, and freeze-thaw repeatedly to obtain a Fe3O4@SiO2-NH2 composite gel; the chitosan solution is a solution formed by dissolving chitosan in acetic acid solution, the concentration of chitosan is 0.04g / ml, the concentration of acetic acid solution is 0.02ml / ml, the concentration of carboxymethyl chitosan solution is 0.02g / ml, the concentration of glutaraldehyde solution is 0.056g / ml, the concentration of polyvinyl alcohol solution is 0.08g / ml, and the mass ratio of chitosan, carboxymethyl chitosan, glutaraldehyde, and polyvinyl alcohol is 120:40:1:
160.
2. The preparation method according to claim 1, characterized in that: In step 1, the mass ratio of Fe3O4@SiO2 to the volume ratio of KH550 was 1:1.1, g:mL.
3. The preparation method according to claim 1, characterized in that: In step 2, the freeze-thaw cycle is repeated more than 3 times.
4. The preparation method according to claim 1, characterized in that: In step 2, during the repeated freezing and thawing process, the freezing temperature is -20°C, the freezing time is 24 hours, the thawing temperature is 26°C, and the thawing time is 4 hours.
5. The Fe3O4@SiO2-NH2 composite gel prepared according to the preparation method according to any one of claims 1 to 4.
6. Use of the Fe3O4@SiO2-NH2 composite gel according to claim 5 in soft robots.
Citation Information
Patent Citations
Preparation method of polyvinyl alcohol magnetic hydrogel
CN108530653A
Preparation method of magnetic carboxymethyl chitosan adsorbent
CN109046265A